2003
DOI: 10.1590/s0066-782x2003001100005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dyslipidemia and risk factors in Campos dos Goytacazes, in the Brazilian State of Rio de Janeiro

Abstract: OBJECTIVE: To determine the prevalence of dyslipidemias in adults in the city of Campos dos Goytacazes, in the Brazilian state of Rio de Janeiro, and to identify its relation to risk factors. METHODS: Cross-sectional, population-based, observational study with sampling through conglomerates and stratified according to socioeconomic levels, sex, and age, with 1,039 individuals. Risk factors, familial history, blood pressure, anthropometric measurements, glucose, triglycerides and cholesterol were determined. RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
28
2
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 31 publications
11
28
2
7
Order By: Relevance
“…Curiously that finding did not occur in the comparison between eutrophic and obese individuals. The study by Souza et al 23 , which assessed the prevalence of dyslipidemia in other region of Brazil, showed a significant statistic difference in the prevalence among individuals with and without overweight. However, the same was not seen in relation to obesity.…”
Section: Discussionmentioning
confidence: 96%
“…Curiously that finding did not occur in the comparison between eutrophic and obese individuals. The study by Souza et al 23 , which assessed the prevalence of dyslipidemia in other region of Brazil, showed a significant statistic difference in the prevalence among individuals with and without overweight. However, the same was not seen in relation to obesity.…”
Section: Discussionmentioning
confidence: 96%
“…Migration to urban centers and adoption of a sedentary lifestyle is likely related to rising lipid levels and prevalence of dyslipidemia [16]. Regional variations in the prevalence of dyslipidemia were previously reported in national and international studies [5][6][7][8]26,27] and may be due to other variables in addition to geographical location. The associations between dyslipidemia and male gender and advancing age detected in this study are in agreement with previous studies in the KSA [5][6][7][8] and other population-based and hospital-based studies [19,[21][22][23].…”
Section: Physical Activitymentioning
confidence: 99%
“…It is emphasized, however, that the drivers' age was relatively younger, which may evidence early lipid alteration, as a result of their inadequate lifestyle (22)(23) . As for life habits, particularly alcoholic beverage consumption, findings were similar to two Brazilian studies in the same professional group (22)(23)(24) , but higher when compared with population-based studies in the South of Brazil (25) .…”
Section: Resultsmentioning
confidence: 99%